Microencapsulation of essential oils with biodegradable polymeric carriers for cosmetic applications - Isabel M. Martins (2014)
Microencapsulation provides an important tool for cosmetic and/or pharmaceutical industry, enabling protection and controlled release of several active agents. The encapsulation of essential oils in core-shell or matrix particles has been investigated for various reasons, e.g., protection from oxidative decomposition and evaporation, odor masking or merely to act as support to ensure controlled release. A large number of microencapsulation methods have been developed in order to be adapted to different types of active agents and shell materials, generating particles with a variable range of sizes, shell thicknesses and permeability, providing a tool to modulate the release rate of the active principle. With this work, an overview regarding properties and applications of essential oils and biodegradable polymers in the cosmetic field, focusing the use of polylactide as the base material to encapsulate thyme oil, as well as of microencapsulation processes with a particular emphasis on the coacervation, will be presented.